TEXTILE SLUDGE: A VALORIZATION ANALYSIS WITH CPQVA SYSTEMATIC - Miotto, Wanessa; Goulart de Oliveira Maia, Bianca; Sellin, Noeli (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
The textile industry is a pioneer in innovation, striving for sustainability in its processes. During manufacturing, textile sludge is generated, the composition of which varies depending on the product and effluent treatment. In Brazil, approximately 73,000 tons of this waste are generated annually. Much of it is sent to landfills, and in some cases, it is believed to be improperly discharged into water bodies, causing increasing environmental problems. This study evaluated ways to valorize textile sludge using the CPQVA (Classification, Potential, Quantity/Feasibility, and Applicability) system, a decision-making system for valorizing industrial waste. Initially, a literature review was conducted using an artificial intelligence tool, covering studies that applied the CPQVA system and valorized textile sludge in three areas: agriculture, construction, and energy generation. Four studies were filtered for each area. Subsequently, sludge samples were collected from a textile industry for characterization and quantification. Using this data, the CPQVA system was applied, considering the company’s interests. For each criterion, 12 questions were answered, weighted according to their level of importance, and the responses were weighted according to the difficulty in valorizing the waste. Criticality indices were calculated for each criterion and the total index. The results indicated criticality indices of 3.28 for ceramic products in civil construction (blocks, non-structural concrete, and asphalt), 3.37 for biomass briquettes, and 3.08 for substrate for anaerobic co-digestion. Thus, the CPQVA system demonstrated that these products have high potential for valorizing textile sludge.